(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
Loneliness is a socio-psychological state characterized by a lack of contact with society, an individual’s emotional disinterest, and alienated behavior. Loneliness can be considered a social disease, which affects a lot of individuals who experience such a condition. The level of loneliness is not related to the number of years a person has spent out of communication; people who live alone throughout their lives sometimes feel less lonely than those people who often have to be among people and contact them. It is impossible to call a lonely person who does not show loneliness reactions, communicating little with others. this article is devoted to the theoretical consideration of the psychology of loneliness. It analyzes the types of loneliness of S.G.Korchagina